Mission Mode Implementation of E-Government Initiatives and the Growth of E-Governance in the State of Kerala: Successes and Challenges in Implementing E-Government Initiatives in Kerala (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Kerala, being the number one literate State in India is now the number one digital literate state also. The mission mode programme implementations up to date could establish Kerala a leading IT destination in India. The judicious implementation of a handful of information and communication technology-based government initiatives allowed an improved participation in the e-government by the common people and also generated direct and indirect employment opportunities to them in the information and communication sector. These initiatives also motivated to improve the socio-economic development of the state. Kerala could succeed to build an excellent e-governance administration model in the State, by its tireless efforts since 1990’s to till date. The different governments that ruled in Kerala for many years paid more attention in bringing the state’s digitalisation a success. The governments were successful in this venture because of the integration of various necessary conditions desirable for the creation of a well-developed e-government in the state. The different governments that ruled in Kerala since 1990 focused on capacity building, infrastructure creation, industry support and creation of e-government applications through different mission mode programmes which are use fulat large for the people of Kerala.